Photoanthropometric Study of Nasal Angles in Adult Bangladeshi Population (Bangladesh Journal of Anatomy, 2019)
Context : Photo-anthropometric measurement of nasal angles are used to determine sexual dimorphism. These angles are necessary to perform optimum correction of shape of nose in both sexes during rhinoplasty. Any surgeon who performs rhinoplasty should be keenly aware of the sex and racial/ethnic differences in nasal anatomy. So far it is known, there is no published article on this topic in Bangladesh. So this study was done to determine the nasal angles and to compare the angles of the nose between male and female in adult Bangladeshi population. Materials and Methods: The standard digital photographic images were taken in right lateral view from 200 consented medical students (100 male and 100 female) of Sir Salimullah Medical College, Mugda Medical College and Green Life Medical College, Dhaka, Bangladesh aged between 20 to 25 years without any history of facial deformities and injuries. These images were transferred to a computer and from these images nasofrontal angle, nasal tip angle and nasolabial angle were measured by MB ruler software. Results: The mean±SD of the nasofrontal angle, nasal tip angle and nasolabial angle were 123.27±4.18° , 81.09±3.49° and 94.94±4.12° respectively in male and 131.83±5.51°, 82.85±3.58° and 97.43±4.41 respectively in female. All three angles were significantly higher in female than in male (P < 0.001).Bangladesh Journal of Anatomy January 2019, Vol. 17, No. 1, pp. 25-29